2004
DOI: 10.2134/agronj2004.1588
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Relationships between Cotton Yield, Quality, and Soil Properties

Abstract: most common ways to describe the relationship between two or more variables. Correlation coefficients are a mea-Intercorrelation among soil properties can result in multicollinearsure of the degree of linear association between any two ity problems regarding relationships between soil properties and crop yield. The objective of this study was to compare statistical methods variables when other variables are fixed. The regression of examining relationships between cotton (Gossypium hirsutum L.) model can indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 20 publications
1
31
0
2
Order By: Relevance
“…To solve multicollinearity problems between independent variables, several authors applied partial least squares regression (PLS) (Corwin et al, 2003;Ping et al, 2004). Loadings from linear combinations of variables in PLS allowed identifying soil properties that have the greatest influence on yields.…”
Section: Introductionmentioning
confidence: 99%
“…To solve multicollinearity problems between independent variables, several authors applied partial least squares regression (PLS) (Corwin et al, 2003;Ping et al, 2004). Loadings from linear combinations of variables in PLS allowed identifying soil properties that have the greatest influence on yields.…”
Section: Introductionmentioning
confidence: 99%
“…3. The stepwise regression (SR) and principal component analysis (PCA) of the multispectral dataset from field 1 for the three studied dates were also performed to reduce multi-collinearity between independent variables (Ping et al 2004) and to determine the combined relationship of all the spectral variables on yield. The correlation matrix was used to calculate the eigenvalues and the eigenvectors for the PCA.…”
Section: Discussionmentioning
confidence: 99%
“…The good relationship among the studied soil characteristics was extracted in the form of the following equation that produced a R 2 of 0.892 and RMSE of 0.093, Fig (4). Olive yield = 1.48571 + 0.00314*Depth -0.00914*Gravels -0.00918*Sand + 0.03213*Silt + 0.00729*Clay + 0.01542*Salinity -0.04413*pH -0.00863* CaCO 3 Whereas the output from the linear combination of variables in PLSRM, stated by (Ping et al, 2004), allows identifying soil properties that have the greatest influence on yield. Accordingly, the current study indicated that most influencing soil properties could be arranged in the order of; gravel, depth, silt, sand, carbonate, and clay, while salinity and pH are not having significant influences.…”
Section: -Soil Characteristicsmentioning
confidence: 99%
“…However, neglecting some variables could contribute to missing important information. Several authors have applied partial least squares regression (PLS) to overcome the multicollinearity problems between independent variables (Corwin et al, 2003); (Ping et al, 2004). Running linear combinations of variables in PLS allowed to identify soil properties that own the greatest influence on yields.…”
Section: Introductionmentioning
confidence: 99%